Study of Sky Radio Frequency Interference Background Level Behavior During the Partial Solar Eclips on 25 Oct. 2022 at The Baghdad University Location - Zina Fadel Kahdim; Kamal M. Abood (Al-Mustansiriyah Journal of Science, 2024)
Radiofrequency interference (RFI) describes the weakening of radio astronomy transmissions caused by man-made radio signal noise in radio telescope observation indicates the level of radio frequency noise in the sky at all times, regardless of any astronomical sources. This noise is affected by various sources, including Earth's atmosphere or solar activity and all communications equipment operating near the radio telescope. In this study, the background noise which includes RFI was measured using HSA2000 series receiver spectrum analyzer, which connected with two dipole antennas in different frequency bands (15-80 MHz) low band antenna, and (110-240 MHz) high band antenna during the partial solar eclipse in Baghdad on October 25, 2022, at (12:00-15:00), as a simple radio telescope to observe the radio astronomical background level in the sky. It is clear that the average amount of RFI level during a partial solar eclipse (-83.249 dBm for LBA decreased by about (0.93) from the value on a normal day (-77.495 dBm). And For HBA -84.711 dBm decreased by about (0.85) from the value on a normal day (-72.784 dBm). Also, it was noticed that these amounts are approximately equal to the RFI level at night (-82.352 dBm for LBA and -82.739 dBm for HBA). It is (0.98) for LBA and (0.97) for HBA, respectively. This research confirms that despite the short duration of the partial eclipse, the average value during the partial eclipse period is close to the average values during the night period due to the decrease in the electronic density of the ionosphere, especially at low frequencies, and the FRI of ground disturbances as a result of the activities of human from the surrounding the monitoring area.  also, found that at the monitoring point, there is a good relationship between the time of the maximum partial eclipse and the peaks of signal gain strength.